Analisis Kualitatif dan Kuantitatif Co-monomer pada Linear Low-Density Polyethylene (LLDPE) Menggunakan FTIR: Evaluasi Model Regresi dan Implikasi Industri - Naila Agitia Ghaisani; Indah Kurniasari (Lembaga Pengembangan Kinerja Dosen, 2026)
Linear Low Density Polyethylene (LLDPE) is a polymer produced through the copolymerization of ethylene with α-olefins such as 1-butene, 1-hexene, and 1-octene. The type and content of co-monomers incorporated into the polymer chain affect the microstructure, crystallinity, density, and mechanical properties of the material, making accurate characterization essential. This study aimed to qualitatively and quantitatively analyze the co-monomer content in LLDPE products using Fourier Transform Infrared Spectroscopy (FTIR) at the Tech Center of PT Lotte Chemical Titan Nusantara. Qualitative analysis was performed based on infrared spectral characteristics to distinguish co-monomer types, while quantitative analysis was conducted by developing linear regression models using the absorbance of the diagnostic band at 771 cm⁻¹ (A771) and the absorbance ratio A771/A1462 against co-monomer content determined by the reference method of ^13C-NMR. The results showed that the absorption band in the 900–700 cm⁻¹ region, particularly at 771 cm⁻¹, was sensitive to variations in short-chain branching resulting from butene incorporation. The developed regression models demonstrated a linear relationship between FTIR parameters and co-monomer content, enabling rapid and efficient prediction of co-monomer concentration. The absorbance ratio approach provided better stability against variations in sample thickness and spectral baseline fluctuations compared to the direct absorbance method. Therefore, FTIR can be utilized as an effective supporting method for routine analysis of co-monomer content in LLDPE products and can support quality control, product specification validation, and trade classification based on co-monomer content.